Removable transduodenal bypass: development of a new endoscopic concept: research article - Finze, Alida; Otto, Mirko; Kähler, Georg (Visceral medicine, 2023)
Introduction: Obesity and obesity-related disease such as diabetes mellitus type 2 are a permanently rising concern worldwide. Current effective therapeutic options mostly include medication and surgery, but there is a lack of effective treatment options between medication and surgery. Previously, devices such as EndoBarrier® have been placed on the market. However, high complication rates, especially liver abscesses, were seen in patients after implantation of the device. Nevertheless, duodenal lining seems to be an effective therapy for type 2 diabetes in obese patients and can lead to weight loss. Methods: A new removable transduodenal bypass was developed and tested on a porcine model. In this course, the device evolved in its mechanism and handling. The device is designed to avoid typical complications seen in previous duodenal liners. Results: After further development of the device, implantation and use were feasible and safe in the porcine model. Autopsies showed that the device stayed in place and remained intact. Discussion: The new removable transduodenal bypass aims to be a removable therapeutic option for diabetes mellitus type 2 and obesity, replacing previous duodenal lining devices. Use and handling of the device, however, are yet to be tested in the human model in the future.
Online veröffentlicht: 14. Juli 2023
Gesehen am 28.03.2024